(untitled) (TSUL LEGAL REPORT, 2026)
In this article, the doctrinal views on understanding the legal nature of the conflict of interests in the activities of state civil servants are analyzed based on the scientific opinions and views of national and foreign scientists. In the article, the field of public civil service was selected as the main fundamental basis, and the cases related to the conflict of interests in it were discussed. At the same time, the international and national documents describing the conflict of interests were analyzed, and the problems in the system were discussed on the basis of a scientific discussion. In the research work, each case is analyzed from a scientific point of view using methods such as logic, systematicity, comparison, induction, and deduction. At the end of the research, the issues of preventing conflicts of interest in the state civil service were substantiated from a scientific and theoretical point of view, and suggestions and recommendations were developed regarding the improvement of the activity. Moreover, it was concluded that the conflict of interests as a form of corruption is a socio-legal problem that seriously damages the state administration and the rights and interests of citizens. As a general conclusion, a conflict of interest is recognized as a conflict that occurs between the powers of a civil servant and his personal interests. The author’s personal position regarding the object of research is stated, and the definition of authorship is developed regarding the topic.